A solution-processed, ultraviolet-irradiation-derived WO3 film as anode interface layer for high-performance non-fullerene organic solar cells. (1st March 2021) - Zhan, Tao; Ren, Peng; Huang, Xiaofang; Zhang, Xiuyun; Chen, Guiting; Xiong, Jian; Xue, Xiaogang; Cai, Ping; Zhang, Jian; Chen, Junwu
Highlights: A solution-processed, ultraviolet-irradiation-derived WO3 layer is developed. The work function of ITO/WO3 is increased to 5.13 eV from 4.76 eV of bare ITO. ITO/WO3 shows more uniform and hydrophobic surface compared to bare ITO. ITO/WO3 -based devices exhibit excellent efficiency of 8.70%. Abstract: Tungsten(VI) oxide (WO3 ) with excellent charge transport properties and intrinsic thermal and chemical robustness is a promising anode interface material instead of PEDOT:PSS in organic solar cells (OSCs). Herein, a solution-processed, ultraviolet-irradiation-derived WO3 film as anode interface layer (AIL) is developed based on tungsten(VI) chloride (WCl6 ) as precursor. The WO3 film is derived from the solution-processed precursor film with simple ultraviolet-irradiation treatment, and the preparation process without high-temperature annealing is very compatible with large-scale production and flexible substrate. The composition of the WO3 film is analyzed by X-ray photoelectron spectroscopy. ITO modified by the WO3 film, namely ITO/WO3, exhibits similarly high optical transmittance as that of bare ITO. The work function of ITO/WO3 measured by ultraviolet photoelectron spectroscopy is obviously lower than that of bare ITO, which can facilitate effective holes extraction. In addition, the WO3 film possesses relatively smooth and hydrophobic surface, beneficial to form excellent interface contact with active layer. Moreover, non-fullerene OSCs based on the WO3 film as AIL are studied with typical and relatively low-cost PBDB-T:ITIC as active layer. The optimal efficiency (8.70%) of the device based on ITO/WO3 is dramatically higher than that (3.32%) of the device based on bare ITO, and comparable to that (8.80%) of the device based on ITO/PEDOT:PSS. Therefore, the solution-processed, ultraviolet-irradiation-derived WO3 film as AIL should have great potential to realize high-performance non-fullerene OSCs, which can also inspire a novel and promising route to prepare other transition metal oxide films in optoelectronic devices.